2019
DOI: 10.3390/jcm8040493
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating an Invisible Epidemic: A Systemic Review of the Clinical and Economic Benefits of Early Diagnosis and Treatment in Inflammatory Disease and Related Syndromes

Abstract: Healthcare expenditures in the United States are growing at an alarming level with the Centers for Medicare and Medicaid Services (CMS) projecting that they will reach $5.7 trillion per year by 2026. Inflammatory diseases and related syndromes are growing in prevalence among Western societies. This growing population that affects close to 60 million people in the U.S. places a significant burden on the healthcare system. Characterized by relatively slow development, these diseases and syndromes prove challengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 171 publications
0
13
1
1
Order By: Relevance
“…Studies have shown DMTs to reduce relapses, decrease disability, and improve health-related quality of life. 26 In addition, when patients are treated early, DMTs can delay the progression of disease and reduce the number of new lesions 27 and could lead to lower treatment costs, 28 reduced health care utilization, fewer days of work loss, and lower direct and indirect costs. 29 It is important to note that as the cost of DMTs rises and the affordability decreases, patients may be deterred from starting DMTs or be forced to interrupt their therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown DMTs to reduce relapses, decrease disability, and improve health-related quality of life. 26 In addition, when patients are treated early, DMTs can delay the progression of disease and reduce the number of new lesions 27 and could lead to lower treatment costs, 28 reduced health care utilization, fewer days of work loss, and lower direct and indirect costs. 29 It is important to note that as the cost of DMTs rises and the affordability decreases, patients may be deterred from starting DMTs or be forced to interrupt their therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding indirect costs, the range of women with FM who are able to preserve their jobs has been reported to be between 34% and 77% [7,8], and reducing work hours due to the impact of symptoms is a common practice among patients with FM [9]. Altogether, FM is second only to irritable bowel syndrome in its contribution to the approximately $300B in costs that inflammatory diseases and related chronic syndromes are expected to generate in the US in coming years [10]. There is a need, therefore, to optimize the development and the implementation of treatments for FM that, next to early accurate diagnoses and methods to support treatment-adherence, would help to address this burden [10].…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, FM is second only to irritable bowel syndrome in its contribution to the approximately $300B in costs that inflammatory diseases and related chronic syndromes are expected to generate in the US in coming years [10]. There is a need, therefore, to optimize the development and the implementation of treatments for FM that, next to early accurate diagnoses and methods to support treatment-adherence, would help to address this burden [10].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In the United States, inflammatory diseases and related syndromes affect approximately 60 million people. A study conducted by Wylezinski et al 5 elucidated the prevalence, clinical characteristics, challenges and financial impacts of four inflammatory diseases and two related syndromes that had an estimated cost of $90 billion in 2018.…”
Section: Introductionmentioning
confidence: 99%